2017
DOI: 10.1111/puar.12766
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Doing More with Less in the Public Sector: Evidence from a Large‐Scale Survey

Abstract: Since the onset of the Great Recession, "doing more with less" has become a policy mantra. To do more with less, a range of governments have concurrently imposed wage cuts and greater work demands on public employees. This article assesses the impact of these changes on the job satisfaction and work motivation of public employees in 34 European countries. Congruent with previous studies linking income and working hours with job attitudes, the article finds a negative impact on both. There are no free austerity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…Scholars have inquired about factors that account for differences in response to community-based action among different organizations and examined why individuals within an organization with similar occupations present different approaches (Christensen, Laegreid & Rykkja, 2016;Drabek & McEntire, 2003;Wenger, 1992). In addition, more generally, what motivates public managers to go above and beyond their formal job requirements (Resh, Marvel, & Wen, 2017), and how can public employees be motivated to do "more with less" (Esteve, Schuster, Albareda, & Losada, 2017). Differences in individual responses to crises are generally shaped by their immediate organizational arrangements and extending to features of the policy community within which they operate.…”
Section: Local Efforts and Disaster Response And Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have inquired about factors that account for differences in response to community-based action among different organizations and examined why individuals within an organization with similar occupations present different approaches (Christensen, Laegreid & Rykkja, 2016;Drabek & McEntire, 2003;Wenger, 1992). In addition, more generally, what motivates public managers to go above and beyond their formal job requirements (Resh, Marvel, & Wen, 2017), and how can public employees be motivated to do "more with less" (Esteve, Schuster, Albareda, & Losada, 2017). Differences in individual responses to crises are generally shaped by their immediate organizational arrangements and extending to features of the policy community within which they operate.…”
Section: Local Efforts and Disaster Response And Recoverymentioning
confidence: 99%
“…Scholars inquire about why individuals within an organization with similar occupation adapt different approaches to managing crises, what motivates certain individuals to go above and beyond their formal job requirements (Resh et al, 2017), and how can public employees be motivated to do "more with less" (Esteve et al, 2017). For instance, scholars found that rather than monetary factors, values alignment where public employees' personal values are aligned with their jobs, makes a difference in motivation, attitude, and performance (Esteve et al, 2017). In other words, the pursuit of organizational values and identification with organizational mission becomes more important.…”
Section: Reasoning and Indicatorsmentioning
confidence: 99%
“…When the effects of cutback reach the service delivery level, it is often at the end of a series of decisions on resource allocations, 120 taken sequentially at different levels and in a hierarchical pattern. However, the focus of recent research has typically been on central government policy (Ghin, Hansen, and Kristiansen 2017;Van de Walle and Groeneveld 2016), and human resource strategies (Esteve et al 2017;Kim 2018;Park 2018), with less attention to cutback management on the front line. A recent cutback management study which did focus 125 on the service delivery level commented on the lack of systematic research at the agency and 'street level bureaucrat' level in fiscal crisis (Savi and Cepilovs 2017).…”
mentioning
confidence: 99%
“…Schmidt, Groeneveld, and Van de Walle (2017) add a third approach by drawing on the work of Pollitt (2010), namely organisational changes aimed at increasing efficiency. This third approach is akin to the popular phrase 'do more with less' (Hood 1991;Esteve et al 2017) and efficiency is one of the three Es, 145 alongside effectiveness and equity, which have commonly been used for assessing the performance of public services (Savas 1978;Andrews and Entwistle 2010). The focus of cutback, and the issues to consider under each of these aims, draws from a range of different cutback management sources (summarised in Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation